Franklin in his own time : a biographical chronicle of his life, drawn from recollections, interviews, and memoirs by family, friends, and associates - Hayes, Kevin J.; Bour, Isabelle (Writers in their own time (University of Iowa Press), 2011)
In his time Benjamin Franklin (1706-1790) was the most famous American in the world. Even those personally unacquainted with the man knew him as the author of Poor Richard's Almanack, as a pioneer in the study of electricity and a major figure in the American Enlightenment, as the creator of such life-changing innovations as the lightning rod and America's first circulating library, and as a leader of the American Revolution. His friends also knew him as a brilliant conversationalist, a great wit, an intellectual filled with curiosity, and most of all a master anecdotist whos.